The Role of the Indonesian National Army (TNI) in the Total People's Defense and Security System (SISHANKAMRATA) in Facing Hybrid Threats - Hendra, Hendra; Sumertha, I Gede; Suharto, Priyanto (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
The outcome of the 21st Century SISHANKAMRATA National Conference produced a strategic document encompassing doctrines, strategies, and the posture of the Indonesian National Armed Forces (TNI), formulated to adapt to the evolving spectrum of future threats or warfare, such as hybrid threats. This article examines the extent to which the Indonesian Army (TNI AD) responds to hybrid threats based on the strategic document of the 21st Century SISHANKAMRATA through a people-based, territorial, and total defense system. This study employs a qualitative method using a library research approach, with the aforementioned strategic document serving as the primary reference in analyzing the role of the Indonesian Army in addressing hybrid threats. The findings reveal that although SISHANKAMRATA has been well-formulated in accordance with 21st-century developments, its implementation remains limited and faces significant challenges, particularly regarding budget constraints in establishing defense capabilities on major islands and fulfilling Defense and Security Equipment (ALPALHANKAM) requirements. Therefore, ministries and government institutions acting as main elements, in collaboration with the TNI in facing non-military threats, must mobilize all national resources, namely natural resources (SDA), human resources (SDM), and artificial resources (SDB) to strengthen national defense. This is in accordance with Presidential Regulation No. 8 of 2021 concerning the role of ministries/agencies in conducting early prevention of non-military threats. This study also emphasizes the importance of improving human resource capacity to support the TNI's role in responding to hybrid threats.